2002
DOI: 10.1136/bmj.325.7367.737
|View full text |Cite
|
Sign up to set email alerts
|

Why men with prostate cancer want wider access to prostate specific antigen testing: qualitative study

Abstract: Objectives To explore the attitudes of men with confirmed or suspected prostate cancer to testing for prostate specific antigen. Design Qualitative interview study with a purposive sample. Setting Great Britain. Participants 52 men with suspected or confirmed prostate cancer, recruited through general practitioners, urologists, patient support groups, and charities. Results Almost all men remembered their prostate specific antigen test but recalled being given little information beforehand. Arguments in favour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
8

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 17 publications
0
29
0
8
Order By: Relevance
“…In a small study in Oxford (n = 52), almost all patients analysed remembered having had a PSA test, but stated that they had received little information at the time of the test. 17 More men in our study reported a lack of awareness in the general practice referred group compared to those men tested in secondary care. In the primary care setting when patients present with LUTS or to request PSA testing, there is often insufficient time to have a lengthy discussion to cover all of the ramifications of PSA testing unless the patient books an appointment specifically for prostate cancer screening.…”
Section: Figurementioning
confidence: 68%
“…In a small study in Oxford (n = 52), almost all patients analysed remembered having had a PSA test, but stated that they had received little information at the time of the test. 17 More men in our study reported a lack of awareness in the general practice referred group compared to those men tested in secondary care. In the primary care setting when patients present with LUTS or to request PSA testing, there is often insufficient time to have a lengthy discussion to cover all of the ramifications of PSA testing unless the patient books an appointment specifically for prostate cancer screening.…”
Section: Figurementioning
confidence: 68%
“…Aspects of masculinity such as appearing weak rather than strong and healthy, may be impacting on participation in screening as shown elsewhere in relation to health practices (Connell, 1995;Moynihan, 1998;Courtenay, 2000), and some of these men may require targeted counselling. The uncertainty surrounding treatment and screening for prostate cancer may have acted as a possible barrier to screening in some men (Chapple et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified that patients have experienced information deficits at particular times, for example at initial presentation in primary care [10,11,12], for further investigations at hospital [13] and post initial treatment [14,15,16]. This study interviewed patients about their experiences of care to date and the identified information deficits throughout their care pathways.…”
Section: Discussionmentioning
confidence: 99%